2013
DOI: 10.1007/s13277-013-1305-y
|View full text |Cite
|
Sign up to set email alerts
|

TP53 alterations and colorectal cancer predisposition in south Indian population: A case-control study

Abstract: The objective of the present study was to investigate the association between TP53 gene single nucleotide polymorphisms (SNPs) and colorectal cancer (CRC) predisposition in south Indian population and to evaluate the role of TP53 expression in the pathophysiology of CRC. A genetic association study was conducted in 103 CRC cases and 107 controls of south Indian origin. We genotyped ten selected TP53 SNPs by polymerase chain reaction-sequencing analysis. Haplotype frequencies for multiple loci and the standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This result is in agreement with the some earlier reported studies where no association of p.P47S polymorphism was observed in breast cancer (Alawadi et al, 2011;Al-Qasem et al, 2012), bladder cancer (Santos et al, 2011), gliomas , urinary bladder cancer (Jaiswal et al, 2011), colorectal cancer (Sameer et al, 2010) and primary open angle glaucoma patients (Daugherty et al, 2009). On the contrary, significant association of S47 has been reported in Caucasian lung cancer (Felley-Bosco et al, 1993), Brazilian brain tumor (Almeida et al, 2009) and South Indian colorectal cancer (Singamsetty et al, 2014) patients. It has been reported that the S47 phenotype has a decreased capacity to induce apoptosis, to transactivate two p53 target genes (p53AIP1 and PUMA), and to bind to MAPK1 protein as compared with the wild-type P47 phenotype (Li et al, 2005;Murphy, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result is in agreement with the some earlier reported studies where no association of p.P47S polymorphism was observed in breast cancer (Alawadi et al, 2011;Al-Qasem et al, 2012), bladder cancer (Santos et al, 2011), gliomas , urinary bladder cancer (Jaiswal et al, 2011), colorectal cancer (Sameer et al, 2010) and primary open angle glaucoma patients (Daugherty et al, 2009). On the contrary, significant association of S47 has been reported in Caucasian lung cancer (Felley-Bosco et al, 1993), Brazilian brain tumor (Almeida et al, 2009) and South Indian colorectal cancer (Singamsetty et al, 2014) patients. It has been reported that the S47 phenotype has a decreased capacity to induce apoptosis, to transactivate two p53 target genes (p53AIP1 and PUMA), and to bind to MAPK1 protein as compared with the wild-type P47 phenotype (Li et al, 2005;Murphy, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The p.P47S polymorphism has been investigated in various cancers including breast (Alawadi et al, 2011), colorectal (Sameer et al, 2010), gliomas , bladder (Santos et al, 2011), brain (Almeida et al, 2009) and urinary bladder (Jaiswal et al, 2011) cancer. Significant association of S47 has been reported in Caucasian lung cancer (Felley-Bosco et al, 1993) and South Indian colorectal cancer (Singamsetty et al, 2014) patients. So far there is no published report on p.P47S polymorphism in EC.…”
Section: Introductionmentioning
confidence: 95%
“…It was revealed that haplotype A2CCG was associated with a higher CRC risk as compared with the most common haplotype A1GCG, while the four other haplotypes A1CCG, A2GCG, A1GTG and A1GCA were associated with a lower risk28. Another study showed an increased CRC risk for the Pro72/Ser47 haplotype of p53 in south Indian population32. Recently, Kamiza et al found that the CT haplotype (rs1042522/rs12947788) of p53 was related with a reduced CRC risk as compared to the common GC haplotype20.…”
Section: Discussionmentioning
confidence: 96%
“…A major strength of our study is that all cases collected in the current study were restricted to tumors growing within 8 cm of the anal verge which was classified as low rectal cancer, while most previous studies addressed total colorectal cancer29-32. Limited but significant evidences have revealed the influence of tumor sites on the frequency, type and prognostic and predictive role of p53 mutation in CRC10, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was in contrast to the previous report, showing a significant association between the mutant S47 phenotype and cancer risk (Felley-Bosco et al, 1993). S47 allele was also found to be associated with increased risk of developing colorectal cancer in South Indian population (Singamsetty et al, 2014). It has been reported that the S47 phenotype has a decreased capacity to induce apoptosis, to transactivate two (p53AIP1 and PUMA) p53 target genes, and to bind to MAPK1 protein as compared with the wild-type P47 phenotype (Li et al, 2005;Murphy, 2006).…”
Section: Discussionmentioning
confidence: 97%